Immunotherapy with B cell epitopes ameliorates inflammatory responses in Balb/c mice. (26th November 2014) - Sharma, P; Gaur, S N; Arora, N
Summary: Osmotin, a protein from the pathogenesis-related family (PR-5), has been identified as an allergen based on in-silico and in-vitro studies. In the present study, three B cell epitopes of osmotin with single and double amino acid modifications were studied for immunotherapy in a murine model. The single-modification peptides (P-1-1, P-2-1 and P-3-1) and double-modification peptides (P-1-2, P-2-2 and P-3-2) showed significantly lower immunoglobulin (Ig)E binding with patients' sera compared to osmotin ( P < 0·01). These peptides showed reduced IgE binding compared to the unmodified peptides (B cell epitopes) P-1, P-2 and P-3. Among the modified peptides, P-2-1, P-3-1, P-2-2 and P-3-2 showed significant reduction in IgE binding and were used for immunotherapy in mice. The sera of mice group treated with peptides showed a significant increase in IgG2a level and a significant decrease in IgE and IgG1 levels ( P < 0·05). The mice that received peptide immunotherapy showed a shift from a T helper type 2 (Th2) to Th1 type where interferon (IFN)-γ and interleukin (IL)-10 levels were elevated, with a significant increase in groups treated with peptides P-3-1 and P-3-2 ( P < 0·05). There was a reduction in the IL-4 and IL-5 levels in bronchoalveolar lavage fluid (BALF) in the peptide-treated mice groups. Total cell count and eosinophil count in BALF of the peptide-treated groups was also reduced compared to the phosphate-buffered saline (PBS)-treated group. Lung histology showed a significant reduction in cellular infiltrate in mice treated with P-2-2 and P-3-2 compared to PBS. In conclusion, peptides P-2-2 and P-3-2 lowered inflammatory responses and induced a Th1 response in mice.